Parkinson's Disease: From Genetics to Treatments - Hueng-Chuen Fan; Shyi-Jou Chen; Horng-Jyh Harn; Shinn-Zong Lin M.D., Ph.D. (Cell Transplantation, 2013)
Parkinson's disease (PD) is a common neurodegenerative disease and typically presents with tremor, rigidity, bradykinesia, and postural instability. The hallmark pathological features of PD are loss of dopaminergic neurons in the substantia nigra (SN) and the presence of neuronal intracellular Lewy body (LB) inclusions. In general, PD is sporadic; however, familial PD, while uncommon, can be inherited in an autosomal dominant (AD) or autosomal recessive (AR) manner. The molecular investigations of proteins encoded by PD-linked genes have clarified that ADPD is associated with α-synuclein and LRRK2, while ARPD is linked to Parkin, PINK1, DJ1, and ATP13A2. Understanding these genes can bring insights into this disease and create possible genetic tests for early diagnosis. Long-term pharmacological treatment is so far disappointing, probably due to unwanted complications and decreasing drug efficacy. Several strategies have been proposed and tested as alternatives for PD. Cellular transplantation of dopamine-secreting stem cells opens the door to new therapeutic avenues for restoration of the functions of degenerative and/or damaged neurons in PD.